The prevalence of suicidal behaviour and associated risk factors in grade 8 learners in Durban - N. Vawda (South African Family Practice)
Objectives: Most of the research on suicidal behaviour in youth focuses on developed countries. Less is known about the prevalence of suicidal behaviour and associated risk factors in community samples of youth who do not present for mental health care in developing countries. This study investigated the prevalence of suicidal behaviour and associated risk factors in grade 8 learners in Durban.